2014
DOI: 10.1016/j.atherosclerosis.2014.05.382
|View full text |Cite
|
Sign up to set email alerts
|

Obesity indices and inflammatory markers in obese non-diabetic normo- And hypertensive patients. a comparative pilot study

Abstract: Background: The aim of this study was to estimate associations between inflammatory markers and obesity indices in normo-and hypertensive subjects. Methods: 65 obese adult subjects were divided into two groups: (A) of hypertensives (n = 54) and (B) of normotensives (n = 11). Waist circumference (WC), body mass index (BMI), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), visceral adiposity index (VAI), body adiposity index (BAI) and tumor necrosis factor-α (TNF-α), interleukin (IL)-6 and high sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 35 publications
2
30
0
2
Order By: Relevance
“…14 Obesity which is a feature of metabolic syndrome was associated with chronic inflammation in obese subjects. 15 In the current study, there is a significant positive correlation of hs-CRP and Total Cholesterol, LDL-C, Triacylglycerol. This is supported by the study done by Mahmoud et al 16 Serum HDL-C was not significantly correlated with hs-CRP.…”
Section: Discussionsupporting
confidence: 52%
“…14 Obesity which is a feature of metabolic syndrome was associated with chronic inflammation in obese subjects. 15 In the current study, there is a significant positive correlation of hs-CRP and Total Cholesterol, LDL-C, Triacylglycerol. This is supported by the study done by Mahmoud et al 16 Serum HDL-C was not significantly correlated with hs-CRP.…”
Section: Discussionsupporting
confidence: 52%
“…We found that the circulatory CRP levels were also elevated in obesity. The present data showing the increased IL-18/CRP expression in obesity are in agreement, at least in part, with previous reports [27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 94%
“…Obesity is associated with chronic inflammation owing to NEFA-induced activation of inflammatory pathways (82,83) . This inflammatory response leads to increased extracellular matrix synthesis but reduced extracellular matrix degradation, resulting in increased deposition and remodelling of extracellular matrix, especially in adipocytes (84,85) .…”
Section: Inflammation Extracellular Matrix and Bone Metabolism-relatmentioning
confidence: 99%